2022
DOI: 10.1097/md.0000000000029316
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical transpedicular screw fixation system in subaxial cervical spine: A finite element comparative study

Abstract: Multilevel cervical corpectomy has raised the concern among surgeons that reconstruction with the anterior cervical screw plate system (ACSPS) alone may fail eventually. As an alternative, the anterior cervical transpedicular screw (ACTPS) has been adopted in clinical practice. We used the finite element analysis to investigate whether ACTPS is a more reasonable choice, in comparison with ACSPS, after a 2-level corpectomy in the subaxial cervical spine. These 2 types of implantation models with the applied 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…However, the maximum stress at the bone-screw interface in the ATPS model was lower than that in the ACLP model during flexion and extension. The stress cloud map indicated that the maximum stress on the screws and plates mainly occurs at the contact area between the screws and plates, consistent with previous studies ( Li et al, 2022 ) ( Figure 6 ). In Table 3 , the maximum stress on the plate in the ATPS model was greater than that in the ACLP model during flexion, extension, and lateral bending, but lower during axial rotation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the maximum stress at the bone-screw interface in the ATPS model was lower than that in the ACLP model during flexion and extension. The stress cloud map indicated that the maximum stress on the screws and plates mainly occurs at the contact area between the screws and plates, consistent with previous studies ( Li et al, 2022 ) ( Figure 6 ). In Table 3 , the maximum stress on the plate in the ATPS model was greater than that in the ACLP model during flexion, extension, and lateral bending, but lower during axial rotation.…”
Section: Discussionsupporting
confidence: 91%
“…Previous investigations have revealed that the pull-out strength of ATPS surpasses that of cervical vertebral body screws (VBS) by 2.5 times, and it can yield comparable outcomes to the combined anterior and posterior surgeries ( Koller et al, 2008b ; Koller et al, 2009 ; Koller et al, 2010 ; Koller et al, 2015 ). Nevertheless, our research team, through a comprehensive series of studies on ATPS, has identified some ATPS limitations, including a heightened risk of screw insertion and technical complexity ( Zhao et al, 2014 ; Zhao et al, 2016 ; Zhao et al, 2018 ; Li et al, 2022 ). Those all curtailed its widespread clinical applicability.…”
Section: Introductionmentioning
confidence: 99%